PENGARUH SUBSTITUSI TEPUNG TIWUL TAWAR INSTAN DAN METODE PENGOCOKAN TERHADAP SIFAT ORGANOLEPTIK SPONGE CAKE. - CHANDRA P, DINKA (Jurnal Tata Boga, 2018)
Abstract Sponge cake is a type of cake made from thick dough and has a slightly coarse texture, less flexible and tend to be camped when cut. This research was aimed to find out 1) the effect of instant tiwul flour on the organoleptic properties of sponge cake tiwul, 2) the effect of shuffling method on sponge cake tiwul result, 3) interaction of instant tiwul flour substitution and whisking method on organoleptic properties of sponge cake tiwul, 4 ) the nutritional value of proximate, iron and calcium in sponge cake. The type of this research is experiment with 3x2 factorial design, where the independent variable is the proportion of tiwul flour: shaking method. Tiwul Flour 45%: Whisking Method cold. 45% tiwul flour: Whisking method is hot. 60% tiwul flour: Whisking method is cold. 60% tiwul flour: Hot whisking method. 75% tiwul flour: Whisking method is cold. 75% tiwul flour: Hot whisking method. The dependent variables of this study include color, aroma, texture, pores, taste, joy. The data was collected using an observation sheet by organoleptic test conducted by 10 trained panelists and 20 semi-trained panelists. Analysis of organolepic test result data using multiple anava test and advanced duncan test. The best results of sponge cake then tested the chemical content proksimat, iron and calcium. The results showed that 1) substitution of instant tiwul flour influenced the organoleptic properties of instant tiwul sponge cake which include color, texture, pores and favorite level. However, it does not affect the smell and taste. 2) shaking method effect on to organoleptic properties of instant tiwul sponge cake which include color. But it does not affect the smell, texture, pores, taste and level of fondness. 3) the interaction of instant tiwul flour substitution and the shaking method have an effect on the favorite level. But it does not affect the color, aroma, texture, pores and taste. 4) nutritional content of the best tiwul sponge cake result of research of 45% instant tiwul flour substitution with cold whisking method. Based on the result of laboratory test in the form of test of proximate chemical content of protein 8.05%, carbohydrate 52.87%, fat 4.90%, fiber 5.11%, water 28.56%, calcium 51.05% and iron 1, 2%. Keywords: Sponge cake, Tiwul flour, Methode whisking.